Land-based sources of seismic signals; Mechanical Engineering, Automation and Control Systems (MEACS) - Gavrilin A. N. Aleksei Nikolaevich; Chuprin E. A.; Moises B. B. Boris Borisovich; Halabuzar E. A. (2014, 2014)
Title screen